2021
DOI: 10.24252/jmw.v3i1.20291
|View full text |Cite
|
Sign up to set email alerts
|

Manajemen Asuhan Kebidanan Pada Balita Dengan Diare Akut Disertai Dengan Dehidrasi Berat (Literatur Review)

Abstract: Pendahuluan Diare  masih menjadi penyebab mordibitas dan mortalitas yang cukup besar didunia dimana diare merupakan  gejala  infeksi saluran  pencernaan. Penyakit ini  dapat disebabkan  oleh berbagai  bakteri, virus  dan parasit dan bahkan di faktori oleh lingkungan dan perilaku manusia dalam kehidupan sehari-hari. Metode Jenis penelitian ini adalah studi kepustakaan dan pengumpulan referensi yang kemudian dibuat menjadi Literatur review dengan menggunakan metode asuhan 7 langkah Varney. Hasil Didapatkannya as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…This occurs due to the exact mechanism of zinc, namely reducing the water content in the intestinal lumen, which increases or increases the absorption of water and electrolytes. Improving stool consistency can reduce the frequency of defecation, so in this case, it is in line with Manopo's research, which found that consuming probiotics and zinc during acute diarrhea can reduce stool output (Amaliah et al, 2021).…”
Section: Constipationsupporting
confidence: 85%
“…This occurs due to the exact mechanism of zinc, namely reducing the water content in the intestinal lumen, which increases or increases the absorption of water and electrolytes. Improving stool consistency can reduce the frequency of defecation, so in this case, it is in line with Manopo's research, which found that consuming probiotics and zinc during acute diarrhea can reduce stool output (Amaliah et al, 2021).…”
Section: Constipationsupporting
confidence: 85%